2014
DOI: 10.1128/aac.02449-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Tigecycline-Colistin Combination Therapies against Carbapenem-Resistant Enterobacteriaceae

Abstract: We assessed the activity of tigecycline (TGC) combined with colistin (COL) against carbapenem-resistant enterobacteria. Synergy occurred in vitro against the majority of isolates, with the exception of Serratia marcescens. In a simple animal model (Galleria mellonella), TGC-COL was superior (P < 0.01) in treating Escherichia coli, Klebsiella pneumoniae, and Enterobacter infections, including those with TGC-COL resistance. Clinical studies are needed to determine whether TGC-COL regimens may be a viable option.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 31 publications
1
30
2
4
Order By: Relevance
“…Unlike previous in vitro studies which had been conducted in KPC-producing carbapenem-resistant E. cloacae strains, our study focused on metallo-beta-lactamase (IMP and NDM)-harboring XDR E. cloacae strains, providing a fresh perspective compared to previous studies (8,32). In addition, our study investigated the activity of polymyxin B in combination with various antibiotics, which is in contrast to most previous studies, which employed colistin in combination with other antibiotics against XDR E. cloacae (8,9). Polymyxin B was employed in preference to colistin, as it has been shown to have superior clinical pharmacokinetics characteristics for infections (33).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Unlike previous in vitro studies which had been conducted in KPC-producing carbapenem-resistant E. cloacae strains, our study focused on metallo-beta-lactamase (IMP and NDM)-harboring XDR E. cloacae strains, providing a fresh perspective compared to previous studies (8,32). In addition, our study investigated the activity of polymyxin B in combination with various antibiotics, which is in contrast to most previous studies, which employed colistin in combination with other antibiotics against XDR E. cloacae (8,9). Polymyxin B was employed in preference to colistin, as it has been shown to have superior clinical pharmacokinetics characteristics for infections (33).…”
Section: Discussionmentioning
confidence: 91%
“…Polymyxin B plus tigecycline also showed bactericidal effect against both E. cloacae isolates; nonetheless, the reduction in colony count was lower than that of polymyxin B plus carbapenems (32). In another study, Betts et al explored the activity of colistin plus tigecycline against CRE, including a tigecycline-resistant E. cloacae strain, by using standard checkerboard and time-kill assays and a simple invertebrate model (8). They found that colistin plus tigecycline was synergistic against the tigecycline-resistant E. cloacae strain in vitro, with significantly improved survival compared to either antibiotic when administered as a monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A time-kill assay (TKA) was performed by inoculating 5 ϫ 10 TGC in carbapenem-resistant S. marcescens isolates has been demonstrated (8).This fact highlights the strain-to-strain variations in the response to antimicrobial combinations. Synergistic activity between colistin and carbapenems has been found in other studies either by checkerboard or by time-kill assay, although Acinetobacter baumannii and Pseudomonas aeruginosa have been the most common bacteria evaluated, with less in vitro data for Enterobacteriaceae (9).…”
mentioning
confidence: 99%
“…The MBL positive strains are, at present, sensitive to polymyxin B and polymyxin E (Colistin). Colistin may be combined with tigecycline as combination therapy for better results (Betts et al, 2014;Datta and Wattal, 2010). The strains isolated from ICU showed same antibiogram profile indicating the possibility of origin from the same clone, but it needs to be confirmed by DNA sequencing.…”
Section: Resultsmentioning
confidence: 99%